Humour Representation of Socio-Political Issues: Analysing Illocutionary Acts in some Nigerian Social Media Skits (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
The study examines the relationship between humour and illocutionary force in Nigerian social media skits, with particular attention to how digital comedy functions as a medium for socio-political commentary. Drawing on Searle’s (1969) Speech Act Theory, the study investigates how illocutionary acts are deployed in selected Nigerian skits to address pressing national concerns and stimulate critical reflection beyond entertainment. Adopting a qualitative approach, three purposively selected online skits – Fuel Scarcity Wahala, Letter to the Bigots, and Pressing Issues in the Senate, by Mr Macaroni and Lasisi were analysed. The videos, sourced from Facebook and Instagram, were transcribed, and twenty-nine utterances were examined. The analysis reveals four predominant categories of illocutionary acts – directives, assertives, expressives, and commissives, while declaratives were absent. The findings demonstrate that, despite their humorous framing, the skits perform significant socio-political functions by satirising issues such as governance, accountability, fuel scarcity, and electoral politics. Overall, the study shows that Nigerian skit makers strategically exploit illocutionary acts as pragmatic resources to initiate public discourse, promote social awareness, and interrogate power relations within the Nigerian socio-political context.
Keywords: Humour; Social Media; Skits; Pragmatics; Illocutionary Acts